Justice in Jerusalem — Interpreting in Israeli Legal Proceedings - Morris, Ruth (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractThis article discusses the background to present-day attitudes towards interpreting in the Israeli judicial system. It outlines traditional Jewish approaches to language issues in legal proceedings, as well as pragmatic solutions adopted in the early years of the Jewish state. A comparison is provided of interpreting arrangements at the 1961 trial of Adolf Eichmann, the mid-1980s proceedings against Ivan (John) Demjanjuk, and a number of other cases involving non-Hebrew-speaking defendants. The article concludes with a discussion of quality assurance arrangements in "ordinary" - as opposed to "major" cases in the Israeli justice system.